2022
DOI: 10.5114/wiitm.2022.123309
|View full text |Cite
|
Sign up to set email alerts
|

Trans-radial versus trans-femoral approach for cerebral angiography: a meta-analysis of randomized controlled trials.

Abstract: Introduction: Both the trans-radial approach (TRA) and the trans-femoral approach (TFA) have been employed for cerebral angiography, but the relative advantages of these two techniques remain uncertain. Aim: To compare the relative safety and efficacy of the TRA and TFA when conducting cerebral angiography. Material and methods: Relevant studies published up to August 2022 were identified in the PubMed, Embase, and Wanfang databases. The rate of successful cerebral angiography was the primary study endpoint, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Furthermore, the transfemoral approach is not indicated for patients with spinal deformities [ 14 ]. In recent years, with the continuous improvement of interventional diagnosis and treatment technology, more and more medical centres have begun to use TRA as an optional path for nerve interventional diagnosis and treatment, and they even use TRA as the preferred puncture method [ 15 , 16 ]. Authors [ 17 ] reported a meta-analysis about the relative safety of cerebral angiography procedures conducted via transradial and transfemoral approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the transfemoral approach is not indicated for patients with spinal deformities [ 14 ]. In recent years, with the continuous improvement of interventional diagnosis and treatment technology, more and more medical centres have begun to use TRA as an optional path for nerve interventional diagnosis and treatment, and they even use TRA as the preferred puncture method [ 15 , 16 ]. Authors [ 17 ] reported a meta-analysis about the relative safety of cerebral angiography procedures conducted via transradial and transfemoral approaches.…”
Section: Discussionmentioning
confidence: 99%